DELINEATING THE COMPLEX LANDSCAPE: IN-DEPTH EXAMINATION OF CHALLENGES TO DEMOCRACY AND TOLERANCE IN INDONESIA UNDER THE STEWARDSHIP OF ANIES BASWEDAN - Taufik Taufik; Nasrudin; Auliya Citra; Abd Rahman; Rahma Helal Al_ Jbour (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This research paper explores the intricate dynamics surrounding challenges to democracy and tolerance in Indonesia during Anies Baswedan's tenure. Amid Indonesia's rich socio-political history, Baswedan's ascendancy represented a crucial juncture in the nation's democratic trajectory. The study delves into the specifics of Baswedan's leadership, scrutinizing its implications for democratic governance and societal tolerance. The paper unravels the multifaceted challenges from community relations to civic engagement, emphasizing their localized impact on Indonesia's diverse cultural and religious landscape. Additionally, the research projects a forward-looking perspective, investigating potential long-term consequences on political stability and democratic development. Conclusively, the paper proposes evidence-based mitigation strategies, acknowledging the inherent complexities of navigating Indonesia's intricate political landscape under Anies Baswedan's stewardship. This research offers a succinct yet comprehensive analysis, shedding light on the complex interplay of historical legacies and contemporary political dynamics in Indonesia's pursuit of democracy and tolerance under Baswedan's leadership.